Sarcopenia, More Than Just Muscle Atrophy: Imaging Methods for the Assessment of Muscle Quantity and Quality - Vasilevska Nikodinovska, Violeta; Ivanoski, Slavcho (Georg Thieme Verlag KG, 2023)
Sarcopenia, a progressive reduction of muscle mass and function, is associated with adverse outcomes in the elderly. Sarcopenia and muscle atrophy are not equal processes. Low muscle strength in association with muscle quantity/quality reduction is currently the optimal method for assessing sarcopenia. There is a practical need for indirect measurement of muscle strength using state-of-the-art imaging techniques.
Keywords: sarcopenia; muscle quantity and quality; DEXA; computed tomography; magnetic resonance; ultrasound